2021
DOI: 10.31083/j.rcm2203084
|View full text |Cite
|
Sign up to set email alerts
|

Non-ST segment elevation myocardial infarction in the elderly

Abstract: Ischemic heart disease constitutes the leading cause of death in Western countries. The general incidence of acute coronary syndromes (ACS), especially non-ST segment elevation myocardial infarction (NSTEMI), is growing. Advanced age is both a strong risk factor for ACS and an independent predictor of poorer clinical outcomes. Management of this entity is often complex in the elderly, while special attention should be focused on comorbidities and geriatric conditions. This article aims to review clinical prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Demographic information and medical history, including hypertension, diabetes, MI, prior coronary revascularization, stroke, information on medications before and during admission, and the percentage of very old patients were collected from medical records by three experienced data inspectors [ 14 ]. The type of AMI, STEMI or NSTEMI, was recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Demographic information and medical history, including hypertension, diabetes, MI, prior coronary revascularization, stroke, information on medications before and during admission, and the percentage of very old patients were collected from medical records by three experienced data inspectors [ 14 ]. The type of AMI, STEMI or NSTEMI, was recorded.…”
Section: Methodsmentioning
confidence: 99%
“…However, the benefit of routine use of an invasive approach is not as clear in older patients with NSTEMI, with the available evidence showing contradictory results [20]. The After Eighty randomized trial demonstrated a significant benefit of an early invasive approach in older patients with NSTEMI [21].…”
Section: Revascularization Approachmentioning
confidence: 99%
“…Aging is a vital risk factor for its prevalence and poor clinical outcomes. Almost a third of patients admitted for ACS and two-thirds of those dying from ACS are >75 years old (3,4). Multi-comorbidities, complicated coronary artery lesions, and high prevalence of frailty in the oldest-old have increased the risk of re-infarcted, bleeding complications, and mortality when compared to younger patients (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%